At-speed delay testing of synchronous sequential circuits - Pomeranz, I.; Reddy, S.M. ([1992] Proceedings 29th ACM/IEEE Design Automation Conference, 1992)
Methods to test sequential circuits for delay faults are discussed. A method called at-speed testing is proposed for simplifying test application and reducing test length. A value system to allow at-speed testing is developed, and a test generation procedure is presented. The effect of at-speed test application on the path delay fault model is described. Experimental results are presented, demonstrating the applicability of at-speed testing and its effect on test length.< >